Clinical Approach to Neurorheumatology - Miloslavsky, Eli M.; Cho, Tracey A. (Seminars in Neurology, 2014)
Rheumatologic conditions are an important cause of both central and peripheral nervous system pathology. A thorough evaluation for an underlying rheumatologic process is an important component of a patient presenting with neurologic symptoms. In this review, the authors present an approach to evaluating rheumatologic conditions, focusing primarily on the history and physical examination. They focus on the most specific signs and symptoms that may help the neurologist assess whether an underlying rheumatologic process is present. In addition, they discuss the interpretation of such findings with an eye toward narrowing the differential diagnosis and directing further testing.
Keywords: rheumatology; autoimmune condition; clinical approach; vasculitis; lupus; sarcoidosis; Behçet disease